Serum OKS40 Ligand kao biohemijski regulator Th2-dominantne imune aktivacije u astmi: integrisana analiza citokinske mreže: Serum OX40L and Immune Activation in Asthma - Zhu, Ziyi; Li, Shumin (Journal of Medical Biochemistry, 2026)
Background: Asthma is characterized by complex immune dysregulation involving coordinated cytokine and chemokine networks. OX40 ligand (OX40L), a key T-cell co-stimulatory molecule, has been implicated in Th2-mediated inflammation; however, its serum-level biochemical interactions with immune activation pathways in asthma remain incompletely defined.Methods: In this cross-sectional study, serum OX40L and immune activation-related factors were quantified in 82 patients with asthma and 40 healthy controls. Multiplex cytokine analysis was performed to measure Th2-, Th17-, pro- and anti-inflammatory mediators, along with chemokines and total IgE. Lung function indices were assessed by spirometry. Correlation analysis and multivariable linear regression were applied to identify immune factors independently associated with serum OX40L levels.Results: Serum OX40L concentrations were significantly elevated in asthma patients compared with controls and increased progressively with disease severity (all P